Attenuation values of renal parenchyma in virtual noncontrast images acquired from multiphase renal dual-energy CT: Comparison with standard noncontrast CT. Issue 101 (April 2018) - Lin, Yuan-Mao; Chiou, Yi-You; Wu, Mei-Han; Huang, Shan-Su; Shen, Shu-Huei
Highlights: The scanning phase, enhancement pattern, and the degree of enhancement affect VNC attenuation. The attenuation value of VNC is reliable. The VNC can be a replacement for SNC. The VNC has lower noise, but inferior image quality to SNC. Nephrographic phase is optimal for creating VNC images in multiphase renal CT. Abstract: Objectives: To compare the renal parenchyma attenuation of virtual noncontrast (VNC) images derived from multiphase renal dual-energy computed tomography (DECT) with standard noncontrast (SNC) images, and to determine the optimum phase for VNC images. Materials and methods: Twenty-nine men and 16 women (mean age, 61 ± 13 years; range, 37–89 years) underwent dynamic renal DECT (100/Sn140 kVp) were included in this institutional review board–approved retrospective study. There were four phases of the scan, which included noncontrast, corticomedullary (CMP), nephrographic (NP), and excretory phases (EP). The VNC images was generated from CMP, NP and EP. CT numbers of SNC images and VNC images of each phases were measured in the renal cortex and medulla. Mean standard deviation of subcutaneous fat was measured as image noise on SNC and VNC images. Radiation dose was recorded and potential radiation dose reduction was estimated. Results were tested for statistical significance using the unpaired t -test and agreement using Bland–Altman plot analysis. Results: The difference in mean attenuation between SNC and each phase of VNC images were ≤4 HU. The mean attenuation of renal cortex and medulla was 33.2 ± 4.4 HU, and 34.2 ± 4.8 HU in SNC, 33.6 ± 7.6 HU and 31.1 ± 8.3 HU in VNC of CMP, 34.8 ± 8.6 HU and 35.6 ± 8.5 HU in VNC of NP, 31.5 ± 7.6 HU and 32.4 ± 7.5 HU in VNC of EP. In VNC of CMP, the attenuation of the cortex was higher than the medulla (p < 0.05), and the attenuation of medulla was significant lower than that of SNC (p < 0.01). In VNC of NP, the attenuation of renal cortex was higher than SNC (p < 0.05). In VNC of EP, the attenuation of cortex and medulla were lower than SNC (p < 0.05), and inadequate iodine subtraction in collecting system was noted. Image noise was significantly greater in SNC (p < 0.001). Mean radiation dose reduction achievable by removing the SNC was 12.3% ± 0.9%. Conclusions: VNC images from multiphase renal DECT were similar to SNC images. Using the nephrographic phase can gives more comparable VNC images to SNC images in renal parenchyma than other phases.